Answer:
See below for answers and explanations
Explanation:
I assume the function you wrote was
1) The equation for the horizontal asymptote is y=-2 since a function of the form f(x) = a(b^x) + c always has a horizontal asymptote at y = c, so c=-2, therefore the horizontal asymptote equation is y=-2
2) The range is (-∞,-2) since any real value of y that is less than -2 but doesn't equal -2 (since it's not included) will be a solution.
3) The domain is (-∞,∞) since any real value of x will be a solution.
4) The axis that f(x) is reflected over is the x-axis because when you negate a base in an exponential function, that will occur.